The Influence Of Product Innovation, Process Innovation And Service Innovation On The Marketing Performance Of Culinary Msmes In Oku District - Ummi, Nur; Munajat, Munajat; Sari, Yunita (Nomico, 2024)
The industrial sector is one of the important sectors in helping the economy progress, therefore the existence of industry as one of the pillars of the economy in OKU Regency has had an influence on the regional economy, even though demographically the livelihood of the majority of the population is as farmers. The policies implemented by the OKU Regency government in handling industry are directed at increasing industrial and craft growth, production and competitiveness, absorbing labor as well as creating a conducive business climate and increasing market share. The programs implemented to advance industry in OKU Regency are small and medium industry development programs and assistance (grants). Through small and medium industry development programs, we strive to improve the skills of entrepreneurs and craftsmen. Meanwhile, the development policy for the industrial, trade and SME cooperative sectors in OKU Regency is directed at growing, fostering and developing small and medium trade industries and cooperatives. The research method used in this research is a survey method conducted on 100 MSME research in OKU Regency. Analysis of the data processed in the research is primary and secondary data. Primary data is used for linear regression. Secondary data is used to look at MSME data in OKU Regency, while to answer problems, assessment criteria using a Likert scale are used, and to look at the influence of product innovation, process innovation and service innovation using linear regression analysis. Based on the analysis of the results of the research that has been carried out, it can be concluded that the research results show that product innovation, process innovation and service innovation have an influence on marketing performance in OKU Regency.